The Effect Of Image Message Perception On Cigarette Background And The Intention To Stop Smoking Teenagers - Sarah Fadhila Siregar; Putra Apriadi Siregar; Apriliani Apriliani; Rani Elviyanti Siregar; Nur Fadhilah Hasanah (Lembaga Penelitian, Publikasi dan Pengabdian kepada Masyarakat (LP3M) Institut Bisnis dan Komunikasi LSPR, 2021)
Smoking behavior in Indonesia is still high. Health warning for room cigarette smoke is 50% of the surface of cigarette packs, but Indonesia is still a country with cigarette smoke in ASEAN at 40%. This study aimed to determine the effect of cigarette packaged image messages on adolescent smoking intentions in Medan. This study used a cross-sectional method. The number of samples in this study was 68 teenagers in Medan City. This study uses a questionnaire as a primary data aid. Bivariate analysis using the chi-square test. The results showed that there were 52.9% respondents aged 20-21 years and had a general department of 52.9%, as many as 52.9% of respondents in semester 4 were 55.9%. The majority of respondents aged 20-21 years without consuming 1-5 cigarettes/day were 55.6%. Responding to fear of cigarette packaged picture messages and having the intention of smoking as much 14.7%. Respondents were not afraid of the cigarette packaged picture messages and had no intention of quitting smoking as much as 17.6%. It can be detrimental to respondents that with the perception of fear, the message of cigarette packs of images has a risk of 1,885 times the intention to quit smoking than respondents who do not have the perception of fear of the cigarette pack image message. It is hoped that the government will expand the picture message on cigarette packets to increase the desire to quit smoking and reduce the number of smokers in Indonesia.